Analisis Pengendalian Persediaan Bahan Baku Dengan Metode EOQ Di PT Polytech Jaya Industri - trisno, Sutrisno; Arista, Anggia (LPPM Universitas Putera Batam, 2021)
This journal discusses the analysis of bottle cap raw material inventory at PT. Polytech Jaya Industri. Lack of raw material inventory makes production operations in a company unable to run effectively. The problem occurs stems from the need for bottle cap raw materials, the company orders bottle cap raw materials regularly for 4,000 dozen per month. However, the total quantity of 4,000 dozen is not sufficient for production need so the company experiences delay in carrying out the production process because they have to wait for the ordered goods to arrive. This research was conducted to determine the optimal number of bottle cap raw material orders, determine safety stock and time to reorder point. Research in this journal is using the Economic Order Quantity (EOQ) method. With the EOQ method from the analysis results, the number of orders for bottle cap raw materials is 15,367 dozen with a purchase frequency of 3 times per year. The safety stock value is 366 dozen and the ROP is carried out when the raw material inventory in the warehouse is 1,46 dozen. The remaining company costs are Rp. 40,607,218/year.